The Effect of Learning Strategy and Locus of Control on Learning Outcomes by Controlling Early Knowledge - Parulian Sibuea; Marianum (Britain International of Linguistics Arts and Education (BIoLAE) Journal, 2022)
The purpose of this study is to empirically study the phenomena that occur related to learning strategies and locus of control by considering the variables of students' prior knowledge of learning outcomes. This research was conducted at SMA Negeri 1 Air Putih, North Sumatra during August to October 2016, and used experimental research methods. The number of subjects in this study each consisted of 40 students consisting of two treatment classes. While the data analysis technique used ANKOVA at a significance level of 0.05. The results obtained: (1) Indonesian language learning outcomes between groups of students taught with CTL learning strategies are higher than groups of students taught using expository strategies after controlling for initial knowledge, (2) Indonesian language learning outcomes among groups of students who have locus of internal control is higher than the group of students who have external locus of control after controlling for initial knowledge, (3) the effect of interaction between learning strategies and locus of control on Indonesian language learning outcomes after controlling for initial knowledge.